Produção e caracterização de α-amilase produzida por Rhizopus sp. - De Souza, Elisângela Lucio; Hoffmann, Erika H.E.; Castilho, Vanessa M.; De Lima, Viviane A.; Bellini, Márcia Z.; Vinícius D'Arcadia Cruz, M.; Cruz, Rubens (My University, 1996)
A strain of Rhizopus sp. screened among more than 800 filamentous fungi showed great ability to produce a thermostable α-amylase by solid state fermentation. The best production was obtained with a bran moisture content of 40% when the enzyme activity reached 60 EU/g. of medium. During the purification procedures, a column of DEAE-Sephadex A-50 separated the enzyme in two fractions and the larger (85% of the total activity) showed optimum pH in a range from -4.0 to 5.6. Optimum temperature was found at 60-65° C and in this range no loss of activity was observed after 60 min. of treatment in pH 5,0. Its Km and Vm are, respectively, of 5.0 mg/ml of starch and 10,01 uMol of reducing sugar/min./mg. of protein. Its molecular weight was calculated in 64.000 by gel filtration in Sepbadex G-200. The dextrinization power of the enzyme was observed preferentialy on substrates compound by chains with higher ramifications, that is: amylopectin > starch > amylose. Other aspects of the enzyme pattern action are also discussed.
Production and characterization of α-amilase from Rhizopus sp.